Production of medium-chain-length polyhydroxyalkanoate by Pseudomonas oleovorans grown in sugary cassava extract supplemented with andiroba oil - SILVA, Diego Aires da (2015)
Pseudomonas oleovorans were grown on sugary cassava extracts supplemented with andiroba oil for the synthesis of a mediumchain- length polyhydroxyalkanoate (PHAMCL). The concentration of total sugars in the extract was approximately: 40 g/L in culture 1, 15 g/L in cultures 2 and 3, and 10 g/L in culture 4. Supplementation with 1% andiroba oil and 0.2 g/L of (NH4)2HPO4 was performed 6.5 hours after growth in culture 3, and supplementation with the same amount of andiroba oil and 2.4 g/L of (NH4)2HPO4 was performed at the beginning of growth in culture 4. The synthesis resulted mainly in 3-hydroxy-decanoate and 3-hydroxy-dodecanoate units; 3-hydroxy-butyrate, 3-hydroxy-hexanoate; and 3-hydroxy-octanoate monomers were also produced but in smaller proportions. P. oleovorans significantly accumulated PHAMCL in the deceleration phase of growth with an oxygen limitation but with sufficient nitrogen concentration to maintain cell growth. The sugary cassava extract supplemented with andiroba oil proved to be a potential substrate for PHAMCL production.